An immunostimulatory dual-functional nanocarrier that improves cancer immunochemotherapy - Yichao Chen (Nature Portfolio, 2016)
The use of immunostimulatory agents to enhance the efficacy of chemotherapy is a promising strategy in cancer therapy. Here, the authors report on a micellar nanoparticle that can effectively co-deliver chemo- and immunotherapeutics, resulting in an improved in vivoantitumour response.